Resource re‐allocation capabilities in internal capital markets: The value of overcoming inertia - Lovallo, Dan; Brown, Alexander L.; Teece, David J.; Bardolet, David (Strategic Management Journal, 2020)
Abstract Research summary We examine the correlations between financial resource allocation flow between business segments and two measures of overall firm financial performance using a sample of Compustat firms. Our analysis finds a consistent inverted U‐shape (or alternatively, V‐shape) relationship between those measures and firm profitability. Interestingly, nearly all the data lie on the upward sloping part of the curve. Taken together, these results support the notion that flows of financial capital are most often positively correlated with financial performance. Managerial summary A key question for any organization is how reallocating capital across business units is related to overall firm performance. We examine the correlations of firm profitability with a measure of change in year‐to‐year allocations across business units in a data set of several thousand firms spanning 18 years. Except in cases of the most extreme reallocations, our measure of firm reallocation is positively correlated with firm performance. Because we cannot prove causality, we cautiously conclude that our findings are consistent with a story that, in most cases, firms would benefit from greater internal reallocation of capital. The managerial question then becomes “what dynamic capabilities are necessary to increase the flow of resources across business segments?” Policies aimed at increasing allocation flow are likely to be beneficial.